Muslims in Medieval Italy: The Colony at Lucera - Taylor, Julie (Lexington Books, 2003)
Muslims in Medieval Italy: The Colony at Lucera is the history of a Muslim colony in the southern Italian city of Lucera during the Middle Ages. Author Julie Taylor draws on a vast array of primary sources, unpublished manuscripts, and archeological data to provide a detailed account of the lives of Muslims against the backdrop of the social and political complexities of medieval Lucera. Taylor's work illuminates the legal and social status of Muslims in Christendom and the contributions made by Muslims to the economy and defense of the kingdom of Sicily, and it also yields noteworthy insights into Muslim-Christian relations. Muslims in Medieval Italy is a thoroughly researched and absorbing account.